The Kanak Awakening : The Rise of Nationalism in New Caledonia - Chappell, David A., 1946- (Book collections on Project MUSE., 2013)
In 1853, France annexed the Melanesian islands of New Caledonia to establish a convict colony and strategic port of call. Unlike other European settler-dominated countries in the Pacific, the territory's indigenous people remained more numerous than immigrants for over a century. Despite military conquest, land dispossession, and epidemics, its thirty language groups survived on tribal reserves and nurtured customary traditions and identities. In addition, colonial segregation into the racial category of canaques helped them to find new unity. When neighboring anglophone colonies began to decolonize in the 1960s, France retained tight control of New Caledonia for its nickel reserves, reversing earlier policies that had granted greater autonomy for the islands. Anticolonial protest movements culminated in the 1980s Kanak revolt, after which two negotiated peace accords resulted in autonomy in a progressive form and officially recognized Kanak identity for the first time. But the near-parity of settlers and Kanak continues to make nation-building a challenging task, despite a 1998 agreement among Kanak and settlers to seek a "common destiny."This study examines the rise in New Caledonia of rival identity formations that became increasingly polarized in the 1970s and examines in particular the emergence of activist discourses in favor of Kanak cultural nationalism and land reform, multiracial progressive sovereignty, or a combination of both aspirations. Most studies of modern New Caledonia focus on the violent 1980s uprising, which left deep scars on local memories and identities. Yet the genesis of that rebellion began with a handful of university students who painted graffiti on public buildings in 1969, and such activists discussed many of the same issues that face the country's leadership today. After examining the historical, cultural, and intellectual background of that movement, this work draws on new research in public and private archives and interviews with participants to trace the rise of a nationalist movement that ultimately restored self-government and legalized indigenous aspirations for sovereignty in a local citizenship with its own symbols. Kanak now govern two out of three provinces and have an important voice in the Congress of New Caledonia, but they are a slight demographic minority. Their quest for nationhood must achieve consensus with the immigrant communities, much as the founders of the independence movement in the 1970s recommended